SISTEM KEWARISAN ADAT SEMENDO DALAM TINJAUAN HUKUM ISLAM - Fauzi, Moh Yasir (ASAS, 2016)
Abstrak: Customary inheritance law is the law that contains provisions on the lines of the system and the principles of the law of inheritance, of inheritance, the devisor and the heir and the way how the estate was transferred by the owner of the devisor to the heir. Semendo society is one of the main indigenous people in southern Sumatra region is categorized as one of the main adherents of the principle of matrilineal kinship with tunggu tubang traditions they follow. Tunggu tubang accordance with tradition, the eldest daughter became the holder of the right to a family legacy in the form of houses, fields or gardens. How Islamic legal review of the customary inheritance system Semendo this is a study that used the topic of discussion in this paper.Keyword: hukum adat, matrilineal, semendo, tunggu tubang